Development of Carabisatulus Chatbot Learning Media Based on Environment to Improve Science Learning Outcomes - Berlian Hariratul Mahya; Deni Setiawan (Postgraduate, University of Mataram, 2024)
According to the results of observations conducted by researchers at SD Negeri Bakalrejo 1, problems were found in the form of limited learning media and student learning outcomes which were still in the low category in science subject content. Based on this problem, the researcher aims to develop, test the feasibility and test the effectiveness of the environment-based Carabisatulus chatbot learning media on the learning outcomes of class V students at SD Negeri Bakalrejo 1, especially on science lesson content. The type of research used is research and development (RnD) using the Borg and Gall model which was modified into 9 stages. Data collection through observation, interviews, questionnaires and documentation. The results of the product assessment are validation of learning media carried out by experts in the field of materials and media with a percentage of 92.5% and 95% with a classification of